Service Capital as a Condition for the Sustainable Development of Society - Mark Khaykin; Olga Toechkina (International Journal of Technology, 2021)
The article deals with the essential nature of a new economic category – “service capital”. Its formation is the logical result of the beginning of the new stage of functioning of economic systems in a post-industrial society. The processes of sustainable development imply global laws governing global economy performance. The authors substantiate the idea that service capital is an economic category and should be studied by modern economic scientists. Most of all, it is connected with institutional theory and is most closely related to institutional capital as a form of manifestation of human capital. Institutional capital is transformed in conditions of an innovative-type service economy and takes the form of service capital. In contrast to institutional capital, it is characterized by some distinctive features discussed in this article. Service capital circulates in the service sector, the importance of which is constantly increasing at all levels of the economy: the mega-, macro-, meso- and microlevels. The article highlights the levels of functioning of service capital. The service capital of each level has sublevels, depending on the criteria chosen for their classification. The authors show that service capital is a special component of human capital. It is inseparable from its bearer, a person, and functions only together with other structural components of human capital. It is established that service capital has been introduced into all branches and sectors of the modern economy, so it functions as intersectoral and interindustry capital. Lastly, the directions of development of the theory of service capital are formulated.